Differential analysis of policy support in tsunami disaster reduction measure by disaster risk: a case study of a tsunami-prone city in Japan - Jun Sakamoto (Geomatics, Natural Hazards & Risk)
Lessons from the Great East Japan Earthquake, 2011, Japan, the Japanese government enacted a new law on tsunami countermeasures. In preparation for the anticipated Nankai Trough earthquake, local governments facing the Pacific Ocean have tried to protect their cities from tsunami damage, such as building tsunami breakwaters and relocating to higher ground. This study aims to clarify the factors influencing public opinion on land development projects to protect housing and urban facilities from tsunamis. Based on a questionnaire survey, we developed an ordered logit model according to each resident’s degree of tsunami risk. Results found that the tsunami risk level to residents’ homes significantly influenced their support for local government policies to develop tsunami-resistant housing and facilities. Also, there was a tendency to support the policy for those at severe tsunami inundation, those who chose their current homes by referring to hazard maps, those who are planning to move in the future, and those who prioritize disaster prevention or living close to their family home when considering where to move. Therefore, in municipalities with a high risk of tsunami damage, narrowing down the target residents and promoting relocation to higher ground is essential to ensure the project’s smooth implementation.